Determinants of petrol station employees safety practices - Faridzuan Teo, Ariff Azril; Muhammad Arif, Afida Mastura (Malaysian Association of Consumer and Family Economics (MACFEA), 2022)
The purpose of this study is to determine the safety practices of petrol stations employees in the Federal Territory of Labuan and Kota Kinabalu, Sabah. One hundred and sixteen employees participated in this study where they were randomly selected by using simple random sampling. The data were collected through a set of self-administered questionnaires. The results show that all three independent variables (occupational hazard awareness, hazard control methods awareness, and safety attitude) were significantly correlated with safety practices. Further results showed that hazard control methods awareness and safety attitude could explain 57.3 per cent of employee safety practices with hazard control methods awareness contributing the most to safety practices. The findings of this study indicate that strong awareness and attitude are essential in preventing injuries and accidents in the workplace.